Risk Factors for Postprocedural Arterial Ischemic Stroke in Children With Cardiac Disease. Issue 9 (September 2020) - Henzi, Bettina C.; Brotschi, Barbara; Balmer, Christian; Hennig, Bert; Rimensberger, Peter; Perez, Marie-Hélène; Pfammatter, Jean-Pierre; Beghetti, Maurice; Sekarski, Nicole; Datta, Alexandre N.; Fluss, Joel; Faignart, Nicole; et al.
Abstract : Background and Purpose: Cardiac pathologies are the second most frequent risk factor (RF) in children with arterial ischemic stroke (AIS). This study aimed to analyze RFs for AIS in children with cardiac disease and cardiac intervention. Methods: Data were drawn from the Swiss Neuropediatric Stroke Registry. Patients with cardiac disease and postprocedural AIS registered from 2000 until 2015 were analyzed for the cause of cardiac disease and for potential RFs. Results: Forty-seven out of 78 children with cardiac disease had a cardiac intervention. Of these, 36 presented a postprocedural AIS. Median time from cardiac intervention to symptom onset was 4 days (interquartile range, 2–8.5); time to diagnosis of AIS was 2 days (interquartile range, 0–5.8). Main RFs for postprocedural AIS were hypotension, prosthetic cardiac material, right-to-left shunt, arrhythmias, low cardiac output, and infections. Conclusions: In children with postprocedural AIS, time to diagnosis was delayed. Most patients presented multiple potentially modifiable RFs as hemodynamic alterations and infections.